Development of mobile-based risk management application for construction companies: an extreme programming approach - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
This research addresses the complexity and dynamics of risks in construction projects by developing a mobile-based risk management application with Extreme Programming (XP) approach. Critical issues in the construction industry involve high uncertainty, changing project conditions, and the need for adaptive risk management. The research method is structured in three stages, starting with Data Collection through literature studies, surveys, and expert interviews. The second stage involves Application Development with the application of XP, focusing on mobile device integration and continuous iteration. The final stage was User Acceptance Analysis to evaluate user response to the developed application. The results showed that the application effectively identified, assessed, and planned risk mitigation. Features like real-time monitoring, reporting, and analytics provide accurate information for quick decision-making. Although some areas have potential for further development, the User Acceptance Analysis gives an overall positive picture with scores above 80 on each feature. This research contributes to developing an application that can improve the responsiveness, flexibility, and quality of construction project risk management. Integrating mobile technology and the XP approach shows relevance and potential to be applied in the construction industry, hoping to provide practical solutions to unpredictable risk dynamics.